The relationships between festival attachment, memorable festival experience, and revisit intention among Arab tourists towards Jerash Festival in Jordan - Al-Azzam, Mu'ath Hesham Metlak (2023)
This study addresses the lack of research on the revisit intentions of Arab tourists attending the annual Jerash Festival of Culture and Arts in Jordan (JFCA), as well as the influencing factors for these intentions. Notably, recent research has shown increased interest in festival attachment and memorable festival experiences as critical factors influencing these intentions. However, both the direct and indirect relationships between festival attachment and revisit intentions are still under investigation. Furthermore, there is a scarcity of studies examining the relationships among all three variables—festival attachment, memorable festival experiences, and revisit intention—as well as the mediating role of memorable festival experiences between festival attachment and revisit intention. In response to these identified gaps, this study aims to investigate the relationships between festival attachment, memorable festival experiences, and revisit intentions among Arab tourists attending JFCA. Additionally, the study explores the mediating role of memorable festival experiences in the relationship between festival attachment and revisit intentions. The theoretical framework of the study was developed based on the Theory of Planned Behaviour, the Theory of Attachment, and the Event Experience Framework. For the above purposes, a quantitative research design using Structural Equation Modelling (SEM) through Smart-PLS version 3 was selected as the most appropriate. The data was collected using a systematic random sampling of 580 Arab tourists who attended JFCA on September 20, 2021. Based on the analysis, there is a significant positive relationship between festival attachment, memorable festival experiences, and revisit intention. Additionally, there is a significant indirect relationship between festival attachment and revisit intention through memorable festival experiences as the mediator. Practically, the study paves the way for organisers, planners, managers, and festival marketers to plan, develop, and market effective festival tourism strategies. The information obtained from this study will enhance tourists’ festival attachment and memorable festival experiences, which in turn will attract and retain more visitors for the event industry in the future.